2013
DOI: 10.1002/star.201300033
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, functional, textural and colour characteristics of starches isolated from four taro cultivars of North-East India

Abstract: Physicochemical, functional, textural and colour characteristics of starches from four North‐East Indian taro cultivars namely, Ahina, Muktakashi, JCC37 and JCC57 were examined. The starch granules were irregular and polygonal in shape and average size of the granules varied from 2.49 to 3.29 µm. All the cultivars presented A‐type XRD pattern, which is a characteristic of cereal starches. The FT‐IR spectra obtained for the four starch samples were similar in the form and intensity of the major peaks. The gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 59 publications
(103 reference statements)
7
23
0
Order By: Relevance
“…The amylose content of Panchamukhi taro starch was 18.14% and was lower than maize starch with amylose content of 24.20% and the difference was statistically significant. The amylose content observed for Panchamukhi taro starch was higher than those reported by Lu et al and Sit et al for other cultivars of taro of North‐East India, but were in agreement with that reported by Mweta et al and Mepba et al . This might be due to difference in the particular variety of taro of North‐East India.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The amylose content of Panchamukhi taro starch was 18.14% and was lower than maize starch with amylose content of 24.20% and the difference was statistically significant. The amylose content observed for Panchamukhi taro starch was higher than those reported by Lu et al and Sit et al for other cultivars of taro of North‐East India, but were in agreement with that reported by Mweta et al and Mepba et al . This might be due to difference in the particular variety of taro of North‐East India.…”
Section: Resultssupporting
confidence: 90%
“…The PT of Panchamukhi taro starch was found to be 84.1°C which was more than maize starch (Table ) and the difference was statistically significant. The PT of Panchamukhi taro starch was close to that observed by Agama‐Acevedo et al for Mexican taro variety and Sit et al for other Indian cultivars but much higher than those observed by Mepba et al and Jane et al . The PT of maize starch was 78.1°C, which was much lower than that observed by Nwokocha et al .…”
Section: Resultssupporting
confidence: 88%
“…All the samples displayed the same spectra, as indicated by peaks at 570, 1033, 1072, 1319, 1566, 1651, 2885, 2931, and 3433 cm −1 ( Figure 2 a). The peak at 570 cm −1 corresponds to the skeletal mode vibrations of the pyranose ring [ 19 , 25 ]. The characteristic peaks at 1033, 1072, and 1319 cm −1 reflect the stretching of C–O, bending of O–H, and bending of C–H, respectively [ 8 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the method of Sit et al [ 15 ], sweet potato tubers were thoroughly washed, peeled, and cut into small pieces. Slurry was prepared by blending the cut tubers in distilled water (50:50 w / v ) for 3 min using an auxiliary kitchen mixer (St 553 Benson Rd, San Antonio, TX, USA).…”
Section: Methodsmentioning
confidence: 99%